Alabama - Feeney, Kathy 1954- (New York Children's Press, 2002)
Takes the reader on a tour of the state called the "Cradle of the Confederacy," emphasizing its geography, history, government, and culture
Different Countries
Includes bibliographical references (p. 76) and index
1 5 8
Keywords: World History; (3GdYGdes